Understanding (with) Toy Models. (10th July 2017) - Reutlinger, Alexander; Hangleiter, Dominik; Hartmann, Stephan
Abstract: Toy models are highly idealized and extremely simple models. Although they are omnipresent across scientific disciplines, toy models are a surprisingly under-appreciated subject in the philosophy of science. The main philosophical puzzle regarding toy models concerns what the epistemic goal of toy modelling is. One promising proposal for answering this question is the claim that the epistemic goal of toy models is to provide individual scientists with understanding. The aim of this article is to precisely articulate and to defend this claim. In particular, we will distinguish between autonomous and embedded toy models, and then argue that important examples of autonomous toy models are sometimes best interpreted to provide how-possibly understanding, while embedded toy models yield how-actually understanding, if certain conditions are satisfied. 1   Introduction 2   Embedded and Autonomous Toy Models   2.1   Embedded toy models   2.2   Autonomous toy models   2.3   Qualification 3   A Theory of Understanding for Toy Models   3.1   Preliminaries and requirements   3.2   The refined simple view 4   Two Kinds of Understanding with Toy Models   4.1   Embedded toy models and how-actually understanding   4.2   Against a how-actually interpretation of all autonomous toy models   4.3   The how-possibly interpretation of some autonomous toy models 5   Conclusion